Belief heterogeneity in the option markets and the cross-section of stock returns - Borochin, Paul; Zhao, Yanhui (Journal of Banking & Finance, 2019)
Standard deviations of the implied-historical volatility spread, of implied volatility innovations, and of the volatility term structure spread in equity options help explain the cross-section of one-month-ahead underlying stock returns. The explanatory power from standard deviations is robust to the levels of these three variables, volatility of volatility, firm characteristics, and common risk factor models. We find support for interpreting the standard deviations of these option-based measures as forward-looking proxies for heterogeneous beliefs. The negative relationship between our three measures and future underlying returns is consistent with the Miller (1977) overvaluation model which implies that divergence of investor opinions in the presence of short-sale constraints leads to lower expected returns.